Actor network theory in food safety - Eden, Vitalis Ronald; Mahmud @ Ab Rashid, Nor Khaizura; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Nowadays, the incidence rate of foodborne disease has increased and become one of the global burdens affecting all individual ages in South East Asia region. Foodborne disease is responsible for mortality and morbidity worldwide thus affecting socio-economic and quality of life. Major causes of foodborne hazards diseases include diarrheal and invasive infectious disease agent, helminthes and chemicals. However, in developing countries, data and record is insufficient with poor surveillance systems leading to incomplete information on the real burden of foodborne disease. The introduction of Actor Network Theory (ANT) as tools for assessing and analyzing the food safety issues has drawn attention from various researcher as it is proven to be able to point out and identify the human and non human actors which is directly and contingently involved. The interaction between the actors such as a worker in an organization, student in school, and peoples in public provide information that can be used to minimize the risk of foodborne disease. The ultimate use of ANT is it helps the researcher to draw a framework of the source of contamination, agent responsible, factors involved, and idea to control the spread.